Fear of Abandonment: Comparative Process Tracing of Hedging Strategies in Australia and India Amid U.S.-China Strategic Competition - Li, Kening (International Journal of Social Sciences and Public Administration, 2025)
This paper examines how the fear of abandonment has shaped the hedging strategies of Australia and India amid intensifying U.S.-China strategic competition between 2012 and 2022. Drawing on a comparative process-tracing approach, the study introduces an analytical framework that conceptualizes fear of abandonment as a multidimensional strategic anxiety – encompassing the fluidity of security commitments, vulnerability of economic dependence, and scarcity of strategic autonomy. Through case analysis, the paper finds that both countries employ hedging, but diverge in form: Australia adopts an institutional hedging model anchored in alliance loyalty and bureaucratic contradictions, while India pursues a more autonomy-preserving path, marked by selective engagement and non-alignment continuity. These differentiated responses reveal how medium-sized powers recalibrate their strategies to mitigate abandonment risks under structural pressures. The study contributes to the broader literature by moving beyond Southeast Asian-focused analyses and enriching theoretical understandings of hedging through a causally grounded, middle-power perspective.